PERANAN SISTEM INFORMASI AKUNTANSI DALAM PEMBELIAN BAHAN BAKU DAN PEMBAYARANNYA PADA PT. FORMITRA MULTI PRAKARSA - Dwita Riesty Andhani; Deni Wardani (STIE Indonesia Banking School, 2014)
One of the many factors that would make a company to remain competitive in the market is an implementation of an accounting information system that goes well at the company, in order to minimize the occurrence of fraud, particularly in raw material purchasing cycle, and disbursements of transactions which is related to the purchase of raw materials . This research uses a descriptive qualitative method. Elements in this study using the elements of internal control, the structure of the organization, authorization, and recording system, sound practices and quality employees in accordance with its responsibilities. To determine whether the information system is effective or not is by using the COSO (Committee of Sponsoring Organizations of The Treadway Commissions)method. There are 5 components of COSO which is: control environment, risk assessment, information and communication, monitoring, and control activities. After analyzing PT Formitra on that aspect, there is only one factor that is a weakness to the company, which is the absence of separation of functions between the recording of the inventory and control function (protecting) of the inventory.